Between Two Worlds: American New Age Music and Environmental Imaginaries - Ottum, Joshua (MUSICultures, 2019)
This article explores how American New Age music imagines the natural world. Through the lens of releases by composers Will Ackerman and Dr. Steven Halpern, I argue that the inherent flexibility and ambiguity of the New Age genre mimics the shifting positions of environmentally-related concepts such as the sublime, the wilderness, and anthropogenic climate change. By exploring two contrasting approaches to the genre, I will outline distinct narratives that provide opposing views of how environmental phenomena function within the New Age context.